The pursuit of urban justice through transit-orientated development: The potential of the Lansdowne-Wetton Corridor - Van der Merwe, Andri (School of Architecture, Planning and Geomatics, 2017)
South African cities are still facing highly inefficient and inequitable urban forms, established by modernist, and apartheid city models. This has resulted in low density sprawl, fragmented and segregated structures, all contributing to unsustainable and unjust city practices. The City of Cape Town is no exception. Cape Town is a tale of two cities, where the urban and spatial landscapes reflect unequal resource distribution and opportunities. Many of its residents remain trapped in an urban landscape that continues to perpetuate its city structures. More importantly, a rapidly increasing population is contributing to the current urban development patterns that are exacerbating previous social injustices and resource intensive patterns. The city is running out of land, resources, and time to restructure its current form and unsustainable development practices. In the pursuit of urban justice, this dissertation argues that a precondition for changing Cape Town's urban performance, is to limit sprawl, increase densities and restructure towards a more intensive and mixed-use city, that will promote efficient public transportation and decentralise social and economic opportunities. Identifying urban Corridor and transit orientated development is a critical approach to structurally promoting efficient and just city structures; with the focus on the Lansdowne-Wetton Corridor as such, a critical element in the restructuring process. This site can then address the needs of some of the most marginalised communities within Cape Town. The design method and package of plans approach was used to guide this dissertation and implement ideas and proposals in an attempt to demonstrate an example of an alternative to Cape Town's current development patterns, that are continuously perpetuating its inefficient, unjust and unsustainable city structure. The study concluded that past urban planning practices have not changed considerably over the past twenty years and that it is of utmost importance to move towards a new way of thinking and developing. This framework can improve equal access to public transportation, social and economic opportunities and re-introducing place making principles. It is aimed at creating positive performing environments, using performance qualities, sustainability, efficiency, equity, integration, urbanity, choice, safety and a sense of place. By focusing on an integrated public transportation system, the intensification of identified areas, designing walkable areas, the promotion of small scale entrepreneurial activities contributes to increasing the accessibility of economic and social activities for all of Cape Town's residents.